Application of nursing measures based on authorization theory in patients with initial arteriovenous fistula - Zhen Ji; Shuxia Cheng; Yang Han; Songju Zhang; Xuling Zhang; Fang Ling; Huilan Cai; Jinhua Liu (Journal of the Pakistan Medical Association, 2025)
Objective: To evaluate the application effect of nursing measures based on authorisation theory in patients with initial arteriovenous fistula. Method: The prospective randomised control study was conducted at Suzhou Kowloon Hospital Shanghai Jiao Tong University School of Medicine, Suzhou, China from March 2023 to March 2024, and comprised patients with initial arteriovenous fistula admitted to the haemodialysis room. They were randomised into research group RG receiving routine nursing and nursing measures based on authorized theory, and control group CG which received routine care. The internal fistula patency rate, self-management ability, negative emotions, quality of life, incidence of complications and satisfaction with nursing in the groups were compared. Data was analysed using SPSS 20. Results: Of the 76 patients, 38(50%) were in group RG; 21(55.3%) males and 17(44.7%) females with mean age 61.14±6.04 years. There were 38(50%) patients in group CG; 20(52.6%) males and 18(47.4%) females with mean age 61.21±6.13 years. Internal fistula patency rate of RG patients was significantly higher compared to CG patients (p<0.05). Post-intervention, the scores of self-concept, health cognition, self-management awareness, and self-management ability in RG patients were significantly higher compared to CG patients (p<0.05). After nursing, the scores of anxiety and depression in RG patients were significantly lower compared to CG patients (p<0.05). After nursing, the quality of life scores in RG patients were significantly higher compared to CG patients (p<0.05). Compared to CG patients, the incidence of complications was significantly lower (p<0.05), and satisfaction with nursing was significantly higher in RG patients (p<0.05). Conclusion:The application of nursing measures based on authorisation theory in patients with initial arteriovenous fistula could promote self-management ability, improved the quality of life, and reduced the incidence of complications in the patients. Keywords: Initial arteriovenous fistula, Nursing, Authorisation theory, Self-management, Complications.